Vapor-liquid equilibria of ternary mixed-solvents with alkali salt (acetone-toluene-H2O-NaCl system) - Pham, Thuy Phuong Thi (Animo Repository, 2005)
The increasing worldwide demand for electronics, semiconductors and optical devices makes these industries expand all over the world especially in Asia. However, the increase in production is coupled with significant increase in the amount of hazardous spent solvents generated such as isopropyl alcohol (IPA), toluene, acetone, methyl ethyl ketone (MEK) and n-methyl pyrolidone (NMP). They are usually mixed with water in lower quantity to remove adhering dirt, grease and waxes. Traditional distillation is not applicable to these types of mixtures to recover the organic solvents at high purity due to high molecular affinity among these solvents. This work presents another method of separating these solvents by taking advantage of the differences in molecular attraction of the species in the solution in the presence of salt. The VLE and the normal boiling point of the system acetone toluene-water-NaCl at different concentrations of salt were measured. Results showed that the solutions with NaCl boil at lower temperature than those without salt when the concentration of acetone is greater than 40 %-mole. Distillation at lower temperature means substantial amount of energy will be saved making the process more economical. Another interesting finding is the increase in the concentration of the non-polar substance (toluene) in the vapor phase when salt is added. The higher the concentrations of the ions present in solution the greater is the amount of toluene that will separate from the solution. Experimental results proved this hypothesis when at 0.5m of NaCl, the amount of toluene in vapor phase is greater than that in the liquid phase. This finding opens the possibility of using molecular affinity modification for selective separation technique and can be easily expanded to multi-component system.